2021
DOI: 10.1111/pbi.13524
|View full text |Cite
|
Sign up to set email alerts
|

A novel NAC family transcription factor SPR suppresses seed storage protein synthesis in wheat

Abstract: The synthesis of seed storage protein (SSP) is mainly regulated at the transcriptional level. However, few transcriptional regulators of SSP synthesis have been characterized in common wheat (Triticum aestivum) owing to the complex genome. As the A genome donor of common wheat, Triticum urartu could be an elite model in wheat research considering its simple genome. Here, a novel NAC family transcription factor TuSPR from T. urartu was found preferentially expressed in developing endosperm during grain-filling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 108 publications
0
29
0
Order By: Relevance
“…Considering the large gene number and high nucleotide sequence identities (>90%) among members of each SSP type, only the expressed genes that could represent most of the sequence variations in the phylogenetic analyses according to Shen et al . ( 2020 ) were selected in both in vivo and in vitro assays in this work. The DNA sequences of all genes in this work can be found in GenBank and in the genome sequence data of T. urartu and T. aestivum under the following accession numbers: TuODORANT1 (GenBank accession No.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the large gene number and high nucleotide sequence identities (>90%) among members of each SSP type, only the expressed genes that could represent most of the sequence variations in the phylogenetic analyses according to Shen et al . ( 2020 ) were selected in both in vivo and in vitro assays in this work. The DNA sequences of all genes in this work can be found in GenBank and in the genome sequence data of T. urartu and T. aestivum under the following accession numbers: TuODORANT1 (GenBank accession No.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that NAM-ATAF-CUC (NAC) TFs participate in a series of biological processes, including abiotic and biotic stress responses and organ development ( Uauy et al, 2006 ; Xue et al, 2011 ; Liang et al, 2014 ; Borrill et al, 2017 ; Guerin et al, 2019 ). Recently, some NAC TFs (TaNAC019, TaNAC100, and TaSPR) in wheat have been identified to regulate grain storage protein synthesis ( Gao et al, 2021 ; Li et al, 2021b ; Shen et al, 2021 ). TaNAC019, a wheat endosperm-specific NAC TF, binds to the motif ([AT]NNNNNN[ATC][CG]A[CA]GN[ACT]A) in the promoter region of Glu-1 genes.…”
Section: Gene Network Regulating Storage Protein Biosynthesismentioning
confidence: 99%
“…TaNAC019-BI can improve flour processing quality and is an important candidate gene for wheat quality improvement ( Gao et al, 2021 ). However, two recent studies demonstrated that both TaNAC100 and TaSPR function as repressors of seed storage protein expression in common wheat, indicating that further research is needed for better utilization of such TFs in breeding ( Li et al, 2021b ; Shen et al, 2021 ). The TaDME (wheat DEMETER) gene encoding 5-methylcytosine DNA glycosylase on the long arm of group 5 chromosomes suppresses the LMW-GS and gliadin gene expression by activating the demethylation of their promoters in the endosperm ( Wen et al, 2012 ).…”
Section: Gene Network Regulating Storage Protein Biosynthesismentioning
confidence: 99%
“…as NAC-binding motifs using ChIP-seq and RNA-seq in soybean (Glycine max). In wheat, CANNTG (E-box) and ACGCAG serve as NAC-binding motifs (Liu et al, 2020;Shen et al, 2020). We queried the motifs in different promoter regions of TaGBBS1 and TaSUS2 using PLACE (https://www.dna.affrc.…”
Section: Shamimuzzaman and Vodkinthree (2013) Defined G [A/t] G [A/g]...mentioning
confidence: 99%